CONTROL OF STATE OF DISCONNECTED WINDING OF TWO-SPEED INDUCTION MOTOR AND EMERGENCY DE-ENERGIZING - Kovaliova, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Processes in the disconnected winding of two-speed induction motor in case of earth leakages are investigated and analyzed. Principle of control functions of protective suppression of EMF in the disconnected winding as a result of an appropriate alarm signal in RC accession, occurrence at the point of connection between the stator’s winding and its normally earthed body with further disconnection of its three-phase winding are based.